STUDY ON CHEMICAL CONSTITUENTS AND BIOLOGICAL ACTIVITIES OF MILIUSA SINENSIS Finet et Gagnep., (ANNONACEAE) - Thanh Thuỷ, Trần Thị; Hoàng Anh, Nguyễn Thị (Vietnam Journal of Science and Technology, 2012)
SUMMARY Eleven compounds were isolated from the n-hexane and the ethyl acetate extracts of Miliusa sinensis collected in Hoa Binh province. Their structures were elucidated by analysis of MS, NMR spectra and comparison with the published data. They are methoxy flavanones and methylated flavone: pinostrobin (1), 5-hydroxy-7,4’-dimethoxy flavanone (2), 5-hydroxy-6,7-dimethoxy flavanone (3), 5-hydroxy-7,8-dimethoxy flavanone (4), 3,5-dihydroxy-7,3’,4’ trimethoxyflavone (5); two chalconoids: pashanone (6), dihydropashanone (7); one triterpene: 24-methylenecycloartane-3β,21-diol (8); an oxoaporphine alkaloid: liriodenine (9), and stigmasterol (10), β-sitosterol glucoside (11). The bioactivities of the ethyl acetate extract as well as compounds 5and 9were reported.